Proceedings of the 2nd International Conference on PErvasive Technologies Related to Assistive Environments 2009
DOI: 10.1145/1579114.1579172
|View full text |Cite
|
Sign up to set email alerts
|

Using affective avatars and rich multimedia content for education of children with autism

Abstract: Autism is a communication disorder that mandates early and continuous educational interventions on various levels like the everyday social, communication and reasoning skills. Computer-aided education has recently been considered as a likely intervention method for such cases, and therefore different systems have been proposed and developed worldwide. In more recent years, affective computing applications for the aforementioned interventions have also been proposed to shed light on this problem. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 16 publications
0
27
0
2
Order By: Relevance
“…[15] evaluates the implementation of ACALPA edutainment platform for autistic children. The platform uses an affective avatar, synthesized speech and multimedia content (videos, images and sounds) aiming at supporting and facilitating the teacher-child interaction.…”
Section: A Autism Spectrum Disordersmentioning
confidence: 99%
“…[15] evaluates the implementation of ACALPA edutainment platform for autistic children. The platform uses an affective avatar, synthesized speech and multimedia content (videos, images and sounds) aiming at supporting and facilitating the teacher-child interaction.…”
Section: A Autism Spectrum Disordersmentioning
confidence: 99%
“…Mean of the 1st, 2nd, 3rd, and 4th formant [5][6][7][8] Maximum of the 1st, 2nd, 3rd, and 4th formant [9][10][11][12] Minimum of the 1st, 2nd, 3rd, and 4th formant [13][14][15][16] Variance of the 1st, 2nd, 3rd, and 4th formant [17][18][19][20] Skewness of the 1st, 2nd, 3rd, and 4th formant [21][22][23][24] Interquartile range of the 1st, 2nd, 3rd, and 4th formant [25][26][27][28] Range (i.e. maximum-minimum) of the 1st, 2nd, 3rd, and 4th formant [29][30][31][32] 90th percentile of the 1st, 2nd, 3rd, and 4th formant Several observations are made by the research community with respect to the correspondence among features and emotional categories. Previous work [14] has indicated that anger presents an increased pitch, happiness demonstrates an increased intensity, whereas sadness exhibits a decrease in high-frequency energy.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Also, fatigue can be detected in the driver's voice and the driver can be alerted [13]. Other examples of emotion aware systems include support for people with disabilities, such as educational software [8] for people with autism [29] or serious visual impair. Alternative applications deal with emotion detection in games and human-robot interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The utilisation begins with a kind of social stories in virtual environments combined with video modelling for the purpose of enhancing and developing ASD students' conversation skills [36]. A bet is also made on a VR understood as atractive and easily administered sophisticated training packages aimed at promoting learning through diferent contexts [37], continuing with a proposal to make virtual environments more realistic, reproducing the great complexity represented by the human face and achieving the most complete possible reading of the user's features [38].…”
Section: Review Of the Literature On Virtual Realitymentioning
confidence: 99%